Design And Construction Of A Web-Based Food Ordering System Using CodeIgniter 4 (Studi Kasus: Warung Family) - Argia Dzakwan; Tedi Budiman (RISTEC : Research in Information Systems and Technology, 2025)
Advances in information technology have significantly impacted various businesssectors, including the culinary industry, which is now required to innovate through the use ofweb-based systems. The manual food ordering process often leads to various problems, such aserrors in order recording, long waiting times, and inefficient service. Based on theseconditions, this study aims to design and implement a web-based food ordering system usingthe CodeIgniter 4 framework. In its development, this study used the Prototype method, whichallows users to participate directly in the design process by providing input so that the resultingsystem meets actual needs. The research method used was qualitative, with data collectionthrough interviews, observations, and documentation studies at restaurants. The results of thisstudy indicate that the developed system is able to improve the efficiency of the orderingprocess, speed up service to customers, and simplify admins in managing order and transactiondata. With this system, it is expected that operational processes and service quality in culinarybusinesses can improve significantly.